Peran Orang Tua dalam Membangun Komunikasi Keluarga untuk Meningkatkan Moral Gen Z - Karim, Fadillah; Akhyar, Taufik; Astrid, Gita (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
In the current generation, referred to as Gen Z. Many teenagers are characterized by poor morals, bad speech, and despicable behavior. Sidakersa Urban Village has teenagers with lack of moral ethics who cause a lot of problems for their parents. Parents believe that they should practice moral principles in themselves, so that they can raise a generation with good moral behavior in the future. The purpose of this research is to learn more about parents’ intern family communication to improve Gen Z’s morals. This based on the theory of family communication patterns in interpersonal communication, including communication beetween parents and children. The research methodology used is qualitative with data collection techniques in the form of observation, interviews, and documentation. This research shows that parents play an important role in shaping their children’s character and moral values. Parents must be able to act as educator, role models, and protectors and create an open and warm comunnication enviroment. Open comunnication makes it easier for children to share their feelings and experiences, thus strengthening the emotional bond beetwen parents and children. The obstacles faced by parents in empowering Gen Z morally include mismacthes in parenting patterns, differences in generations and values, limited time and attention, environmental influences, and difficulties in developing their children’s moral values.